Reducing False Recognition in the Deese-Roediger/McDermott Paradigm: Related Lures Reveal How Distinctive Encoding Improves Encoding and Monitoring Processes - Huff, Mark J.; Bodner, Glen E.; Gretz, Matthew R. (Frontiers in Psychology, 2020)
In the Deese-Roediger/McDermott (DRM) paradigm, distinctive encoding of list items typically reduces false recognition of critical lures relative to a read-only control. This reduction can be due to enhanced item-specific processing, reduced relational processing, and/or increased test-based monitoring. However, it is unclear whether distinctive encoding reduces false recognition in a selective or global manner. To examine this question, participants studied DRM lists using a distinctive item-specific anagram generation task, then completed a recognition test which included both DRM critical lures and either strongly related lures (Experiment 1) or weakly related lures (Experiment 2). Compared to a read-control group, the generate groups showed increased correct recognition, and decreased false recognition of all lure types. We then estimated the separate contributions of encoding and retrieval processes using signal-detection indices. Generation improved correct recognition by both increasing encoding of memory information for list words, and by increasing memory monitoring at test. Generation reduced false recognition by reducing the encoding of memory information, and by increasing memory monitoring at test. The reduction in false recognition was equivalent for critical lures and related lures, indicating that generation globally reduces the encoding of related non-presented items at study (not just critical lures), while globally increasing list-theme-based monitoring at test.